Effect of Ardu (Ailanthus excelsa) Leaf Powder Feeding on Growth Performance and Economics of Feeding in Pantja Goats (Indian Journal of Animal Production and Management, 2024)
The present investigation was carried out to study the effect of ardu (Ailanthus excelsa) leaf powder  feeding on growth performance and economics of feeding in Pantja goats at Goat Unit, Department  of Livestock Production Management, G.B. Pant University of Agriculture & Technology, Pantnagar.  The study was conducted on a total of sixteen, 6-8 months old kids, which were randomly divided  into four groups (T0- Control, T1- 75% Concentrate + 25% ardu leaf powder, T2- 50% Concentrate +  50% ardu leaf powder and T3- 25% Concentrate + 75% ardu leaf powder). Growth parameters were  studied by observation of body weight at different time periods viz. 0, 15, 30, 45, 60, 75 and 90 days.  The results of the experiment revealed that treatment groups supplemented with ardu leaf powder  had significantly (P
Keywords: Ardu leaves; Economics of feeding; Growth performance; Pantja goats